Carbon-Neutrality Research in China—Trends and Emerging Themes - Wai Ming To; Andy W. L. Chung (World, 2023)
Carbon neutrality is a key human endeavor to deal with global climate while China is the country producing the most publications on carbon neutrality. However, what are the focuses of carbon-neutrality research in China? To answer such an important question, this study adopts a bibliometric approach to analyze carbon-neutrality journal publications from China-based researchers during the period of 2008–2022 using CNKI and Scopus. Results showed that carbon-neutrality publications in Chinese and English journals by Chinese-based researchers increased from 4 in 2008 to 2879 in 2022. In Chinese journals, X.D. Hao was the most productive author with 10 publications. In English journals, Y.K. Zhou was the most productive author with 14 publications. As a whole, the Chinese Academy of Sciences was the most productive institution with 376 publications. Co-occurrence of keywords analysis revealed seven themes in Chinese journal articles, namely, “carbon neutrality and climate change”, “energy transformation”, “peak carbon emission”, “carbon emission and low carbon economy”, “realization path in China”, “hydrogen energy and clean energy”, and “green finance and sustainable development”. In English journals, three major clusters were formed—“carbon, carbon neutralities, emission control, and energy utilization”, “carbon dioxide, carbon neutrals, biomass, and electrocatalysts”, and “China, carbon neutrality, sustainable development, and economic development.” Most extant publications focused on policy and technological development. Emphasis shall be paid to social change and changes in people’s behavior, sectoral carbon emissions, and carbon leakage in future research.